Vitamin D levels and TaqI, BsmI and ApaI variants of the vitamin D receptor gene in coronary heart disease patients with disease debut at different ages - O. A. Bercovich; Zh. I. Ionova; J. Du; O. D. Belyaeva; E. A. Bazhenova; V. V. Miroshnikova; S. N. Pchelina; K. V. Dracheva; O. A. Klitsenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Vitamin D deficiency may be a natural predictor of the onset of coronary heart disease (CHD) and myocardial infarction (MI) at a young age. The results of studies of the various variants association of the vitamin D receptor (VDR) gene with the risk of CHD are contradictory, which leads to the study of genetic variants of the VDR gene as predictors of the onset of the disease at the age of 45 years and younger in the Russian population. The objective was to determine the distribution of TaqI, BsmI and ApaI genotypes of the VDR gene variants and the level of vitamin D sufficiency in CHD patients with different age of onset of the disease and myocardial infarction, among residents of St. Petersburg. Methods and materials. The study included 410 CHD patients and 320 examined patients without CHD clinical signs of comparable age (p>0.05). All patients with CHD underwent coronary angiography. Typing of VDR gene variants was carried out by polymerase chain reaction and subsequent restriction analysis. Determination of the level of 25(OH)D blood serum was carried out by enzyme immunoassay. Results. The level of 25(OH)D in the blood serum of CHD patients was lower than in the control group (15.61±0.52 ng/ml and 20.82±0.69 ng/ml respectively; p=0.001). Severe 25(OH)D deficiency was detected more often in CHD patients and was associated with an increased risk of CHD (23 % and 8 % respectively; p=0.001, OR=3.54 (1.88÷6.67)). The normal level of 25(OH)D sufficiency was more often detected in patients from the comparison group than in CHD patients, and was associated with a decrease of CHD risk (16 % and 4 % respectively; p=0.0002, OR=OR=0,21 (0,09÷0,48)). The presence of the aa genotype and the a allele (ApaI), the bb genotype and the b allele of the VDR gene (BsmI) is associated with an increased risk of CHD and the onset of the disease and MI at the age of 45 years and younger. Conclusions. Severe 25(OH)D deficiency is typical for CHD patients and was associated with an increased risk of CHD. The presence of the aa genotype and the a allele (ApaI), the bb genotype and the b allele of the VDR gene (BsmI) is associated with an increased risk of CHD and with the onset of the diseases and myocardial infarction at a young age. The TaqI variant of the VDR gene is not associated with the risk of CHD.